2019
DOI: 10.3390/su11092554
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Attitudes towards Cycling and Walking on Travel Intentions and Actual Behavior

Abstract: The design and implementation of effective transport policies to reduce car use in urban areas requires a deep comprehension of the factors that influence travel behavior. In this context, psychological factors play an important role in explaining travel-related decisions. The purpose of this paper is to present a study on the effects of cognitive, affective and behavioral attitudes towards the use of walking and cycling on both intentions and real use of cars, public transport, bicycles, and walking. The data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 52 publications
(76 reference statements)
1
14
0
3
Order By: Relevance
“…Mahmood et al ( 2019 ) study revealed intention as dependent factor. Garcia et al ( 2019 ) study likewise addressed intention as dependent factor. The studies by Mahmood et al ( 2019 ) and Garcia et al ( 2019 ) are consistent with this research findings, which treated behavioural intention as significant mediator.…”
Section: Discussionmentioning
confidence: 99%
“…Mahmood et al ( 2019 ) study revealed intention as dependent factor. Garcia et al ( 2019 ) study likewise addressed intention as dependent factor. The studies by Mahmood et al ( 2019 ) and Garcia et al ( 2019 ) are consistent with this research findings, which treated behavioural intention as significant mediator.…”
Section: Discussionmentioning
confidence: 99%
“…Untuk perjalanan harian sekolah, sesaat sebelum melakukan perjalanan sekolah, para remaja pelajar mulai merencanakan kegiatan harian mereka. Banyaknya tempat yang akan dituju dalam keseharian, menjadi dasar pelajar untuk memilih jenis moda transportasi yang sesuai untuk digunakan (García, Arroyo, Mars, & Ruiz, 2019;Stark et al, 2018). Perlengkapan atau barang-barang yang harus selalu dibawa pelajar dalam aktifitas harian mereka, turut mempengaruhi jenis pilihan moda yang sesuai (Gutiérrez, Hurtubia, & Ortúzar, 2020;Terrón-Pérez, Molina-García, Martínez-Bello, & Queralt, 2018).…”
Section: Studi Pustakaunclassified
“…Perlengkapan atau barang-barang yang harus selalu dibawa pelajar dalam aktifitas harian mereka, turut mempengaruhi jenis pilihan moda yang sesuai (Gutiérrez, Hurtubia, & Ortúzar, 2020;Terrón-Pérez, Molina-García, Martínez-Bello, & Queralt, 2018). Namun, kebutuhan waktu tempuh yang dibutuhkan pelajar untuk mencapai tujuan, tetap memainkan peranan pokok dalam perjalanan (Bigazzi & Lindsey, 2019;García et al, 2019;Grigore, Garrick, Fuhrer, & Axhausen, 2018). Kebutuhan fleksibilitas tinggi terhadap kegiatan keseharian, membuat seseorang selalu ingin untuk dapat bebas pergi kemanapun yang mereka inginkan (García et al, 2019;Pojani et al, 2018).…”
Section: Studi Pustakaunclassified
See 1 more Smart Citation
“…While much research has focused on planning, accessibility, and scenario making, less has elucidated the questions of how to prioritize actions, involve stakeholders, and implement new people-oriented, place-based approaches [6]. Going forward, developing tools used in ex-ante methodologies to help cities identify a priori which measures to prioritize locally to achieve their sustainability goals [7], as well as more concretely understanding citizens' environmental and mobility behaviors and attitudes [8,9], can greatly assist cities in transitioning towards sustainable mobility.…”
Section: Introductionmentioning
confidence: 99%